Building a simulator for electric vehicles' charging behaviour - Wang, Bowen (2016)
Electronic Vehicles have been rapidly developing world widely as it is eco-friendly and cost effective compared with traditional car. To call for the usage of electronic vehicles, the government from many countries such as Singapore are planning to build electronic vehicles charging station effectively and efficiently. Many research about allocation strategy and charging behaviour strategy have been conducted. The objective of this project is to develop a simulator to simulator the electronic vehicle charging behaviour using certain strategy and then data can be collected by researchers to evaluate the performance of the strategy. The API is provided so researchers are able to implement simulator with own purpose and most flexibility is given to the researchers. The main parameters of simulator to be set is map setting, car and station setting, car generator setting and traffic data integration. The real time station information and car movement animation on the map are displayed and output of the simulator can be exported to the Excel for the further analysis.